2007
DOI: 10.1097/01.tp.0000266995.93463.0c
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Murine Syngeneic Graft-Versus-Host Disease by Cells of Recipient Origin

Abstract: These results demonstrate that after lethal irradiation and in the absence of donor T cells, T cells of recipient origin can expand and mediate the induction of CsA-induced SGVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Previous studies had demonstrated a significant skewing of the CD4 + T cell population to the CD62L 2 subset (17)(18)(19). This response suggested that the responsive cells were activated in vivo and that few naive precursor cells were present in either the control or SGVHD animals, as evidenced by lack of reactivity of the CD62L + subset.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies had demonstrated a significant skewing of the CD4 + T cell population to the CD62L 2 subset (17)(18)(19). This response suggested that the responsive cells were activated in vivo and that few naive precursor cells were present in either the control or SGVHD animals, as evidenced by lack of reactivity of the CD62L + subset.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the increase of in vitro reactivity of SGVHD CD4 + T cells against microbial Ags, we have demonstrated that an increase in Th1 and Th17 immunity was observed in SGVHD animals (11,12,(17)(18)(19)(20)(21). Th1 and Th17 effector CD4 + T cells have been shown to participate in a variety of models of colon and liver inflammation.…”
Section: Antibiotic Treatment Alters the Immune Responses Associated mentioning
confidence: 90%
See 2 more Smart Citations
“…It has been observed that proportions of CD4 ϩ T cells are increased in colons of SGVHD mice compared with BMT controls and that CD4 ϩ T cells were responsible for the induction of murine SGVHD (3,4,9). The role of CD4 ϩ T cells as effector cells in the induction of murine SGVHD was demonstrated in two sets of experimental studies.…”
Section: Discussionmentioning
confidence: 99%